A terrible glory Custer and the Little Bighorn-- the last great battle of the American West - Donovan, James 1954-
In June of 1876, on a desolate hill above a winding river called "the Little Bighorn," George Armstrong Custer and all 210 men under his command were annihilated by almost 2, 000 Sioux and Cheyenne. The news caused a public uproar, and those in positions of power promptly began to point fingers in order to avoid responsibility. Custer, who was conveniently dead, took the brunt of the blame. The truth, however, was far more complex. This is the first book to relate the entire story, and the first to call upon all the research and findings of the past 25 years--which have changed significantly how this controversial event is perceived. It is also the first book to bring to light the details of the U.S. Army cover-up--and unravel one of the greatest mysteries in U.S. military history.--From publisher description